International Studies Must Be a Social Science: A Friendly Quarrel with PTJ1. (June 2015) - Neumann, Iver B.
Contra Jackson, I am sceptical of splitting the category of phronesis into aesthetic and normative knowledge, for it invites a Kantian understanding of aesthetics as an exercise in detachment. I see scientific disciplines as genres held together by mutual disciplining, which means that they share a certain style. It is hard for me to see how systematic knowledge may emerge without there being some kind of generalisable intent in play. The scholarly ethos focuses on exactly this element of knowledge production. Sociology and ethics conspire to maintain science's monopoly on systematic knowledge production.